Non-pharmacological Therapy in Fibromyalgia - Rozenbajgier, Martyna; Wójcik-Grudzień, Justyna; Pawłowska, Paulina; Ozga-Stachurska, Alicja (Journal of Education, Health and Sport, 2022)
Fibromyalgia (FM) is a syndrome manifested by chronic, generalized muscle and joint pain and symptoms such as sleep problems, mental disorders, mainly depression, which significantly reduces the patients' quality of life. The etiology, pathogenesis, and pathomechanism of symptoms in FM are still not fully understood, which makes the therapeutic options unsatisfactory. Treatment is mainly based on relieving the symptoms of the disease and is based on both pharmacological and non-pharmacological treatments. It seems that the best results are achieved by a combination of cooperation between a rheumatologist, psychiatrist, psychologist and phosiotherapist. The aim of the study is to present the current state of knowledge about the possibilities of non-pharmacological treatment in people with fibromyalgia Standard criteria were used to review the literature data. The search of articles in the PubMed and Google Scholar database was carried out using the following keywords: fibromyalgia, chronic pain, non-pharmacological therapy in fibromyalgia